Economic Governance Improvements and Sovereign Financing Costs in Developing Countries - Abate, Girum (World Bank, Washington, DC, 2021)
Low- and middle-income country governments are increasingly tapping the global debt capital markets. This is increasing the amount of finance available for development, but at a considerably higher cost than traditional external borrowing on concessional terms. Using a novel methodology based on estimating sovereign credit ratings using the Moody’s scorecard, and examining the associations between these ratings and the World Bank’s Country Policy and Institutional Assessment scores, this paper examines how making improvements in the quality of economic policies and institutions can help lower governments’ financing costs. This method aims to overcome the small-sample problem due to the number of rated developing country sovereigns still being relatively limited (although growing). Better economic governance Country Policy and Institutional Assessment scores are associated with better estimated ratings and materially lower financing costs; on average, improvements that are sufficient to increase the Country Policy and Institutional Assessment economic governance indicator score by one point are associated with interest costs that are lower by about 40 basis points, even setting aside the direct impact on ratings of better governance indicators. There are many reasons why improving governance is a good thing. Among them is the potential payoff to the public purse — savings of $40 million or more on a standard $1 billion, 10-year bond.